Природні умови та їх вплив на господарську діяльність населення Нижнього Побужжя в епоху грецької колонізації (VII—V ст. до н. е.) - Ієвлєв, М.М. (Археологія, 1992)
На основі аналізу кліматичних умов Північного Причорномор'я простежується їх вплив на господарську діяльність населення. Статья посвящена вопросу влияния географической среды на хозяйственную деятельность населения в начальный период греческой колонизации Северного Причерноморья и, в частности, района Нижнего Побужья и Поднепровья. Показывается ее влияние на размещение поселений, их величину, делается попытка их классификации. A problem concerning the effect of the geographic environment on economic activities of population at the initial period of Greek colonization of the North Black Sea territories and, in particular, the region of the Bug and Dnieper areas is analyzed. It is shown how the geographic environment influenced arrangement of settlements, their size; an attempt is made to classify the settlements.